ENERGY ANALYSIS OF A SOLAR-OPERATED SWEEPING GAS MEMBRANE DISTILLATION SYSTEM INTEGRATED WITH DIFFERENT WATER VAPOR CONDENSATION CONFIGURATIONS - Kadhim, Abdullah H.; Bamaga, Omar A.; Baz, Zulfa A.; Abu-Hamdeh, Nidal H. (International Journal of Engineering Technologies and Management Research, 2025)
This study examines the energy and performance of a solar sweeping gas membrane distillation (SGMD) unit with different water vapor condensers. The study assesses the efficiency of the SGMD system under different water vapor condensation configurations using only solar energy. The study examines how water vapor condensation configurations affect system productivity, specifically condensed water yield and energy efficiency. The study was conducted in the Mecca area on three occasions: winter, summer, and day. A new model was created to simulate desalination processes, and the research introduced an SGMD unit modeling component to the standard library. The measured and predicted permeate flow values were similar, with peak solar radiation and maximum ambient temperatures. The study yielded good results, with 5,452 W on the latest summer test day and 4,998 W on the latest winter test day. The seawater outflow from the SGMD system was 53-21 degrees Celsius.